Botryosphaeriaceae fungi on apple fruit – identification and sensitivity to fungicides and essential oils in vitro - Milošević, Milica; Stepanović, Jelena; Rekanović, Emil; Stepanović, Miloš (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2025)
Apple production suffers significant economic losses and fruit quality reduction due to fungal pathogens, particularly ones that cause postharvest fruit rot, such as Botryosphaeriaceae fungi. Isolates used in this study were obtained from symptomatic apples and, based on morphological characteristics and sequence analysis of two genes (EF 1-α and β-tubulin), they were identified as Diplodia seriata and Botryosphaeria dothidea. Pathogenicity tests on healthy apple fruits revealed that D. seriata was more aggressive than B. dothidea, with significantly higher average values of lesion diameter and depth. Fungicide sensitivity tests showed that D. seriata was more sensitive to the combination fluopyram + tebuconazole (EC50=0.00023 μg a.i. ml-1), while B. dothidea exhibited higher sensitivity to pyraclostrobin (EC50=0.025 μg a.i. ml-1). With 98.44% and 97.56% percent growth inhibition (PGI) rate of D. seriata and B. dothidea (respectively) at 10 μg a.i. ml-1, the tested combination of fungicides surpassed pyraclostrobin in inhibition potential. Four essential oils (thyme, rosemary, lavender and lemongrass) were also tested for antifungal activity using the fumigant macrodilution method. Thyme oil demonstrated the highest antifungal potential, completely inhibiting the mycelial growth of both species at 0.05 μl ml–¹ of air. Strong inhibition potential was also shown by lemongrass oil with 100% inhibition of D. seriata and B. dothidea mycelial growth at 0.07 and 0.09 μl ml–¹ of air, respectively. Rosemary oil showed a moderate inhibition potential, while lavender oil was the least effective. These findings highlight the inhibiting potential of fungicides against D. seriata and B. dothidea, but they also indicate that thyme and lemongrass essential oils could be used as viable alternatives. Further research is needed to determine their effectiveness in in vivo assays and potential impact on fruit quality and the environment.